A novel ReN/TiAlN multilayer coating on M2 steel by magnetron sputtering: Development and electrochemical behavior - Grisales, M. Alejandro; Giraldo, Francisco; Bolivar, Francisco J.; Bejarano, Gilberto; Echavarría García, Aida Milena (ElSevier, 2022)
By DC magnetron sputtering ReN and multilayers of TiAlN/ReN films were produced. The coatings were deposited onto high-speed steel (AISI M2) samples and silicon wafers. Analysis of the microstructure and phase composition showed that the ReN monolayer, which was the same as the coating used subsequently for the manufacture of the multilayers of TiAlN/ReN, possessed a cubic crystalline structure. The ReN coating had preferential columnar growth in the direction of the plane (111) and presented precipitates of the rhenium oxides ReO2 and ReO3. A detailed study of the electrochemical behavior and corrosion resistance of the coated steel substrate as a function of the number of TiAlN/ReN bilayers was carried out using electrochemical impedance spectroscopy and polarization measurements. The coatings exhibited a relative high hardness and Young's Modulus, and a better performance against corrosion in aqueous media rich in chlorine ions when the bilayer number and period were 5 and 221.2 nm, respectively. It was observed that the formation of rhenium oxide particles influences the electrochemical behavior of coatings.

Mediante pulverización catódica con magnetrón de corriente continua se obtuvieron películas de ReN y multicapas de TiAlN/ReN. Los recubrimientos se depositaron sobre muestras de acero de alta velocidad (AISI M2) y obleas de silicio. El análisis de la microestructura y la composición de fases mostró que la monocapa de ReN, que era la misma que el recubrimiento utilizado posteriormente para la fabricación de las multicapas de TiAlN/ReN, poseía una estructura cristalina cúbica. El recubrimiento de ReN tenía un crecimiento columnar preferencial en la dirección del plano (111) y presentaba precipitados de los óxidos de renio ReO 2 y ReO 3 . Se realizó un estudio detallado del comportamiento electroquímico y la resistencia a la corrosión del sustrato de acero recubierto en función del número de bicapas de TiAlN/ReN mediante espectroscopia de impedancia electroquímica y mediciones de polarización. Los recubrimientos exhibieron una dureza y un módulo de Young relativamente altos, y un mejor desempeño frente a la corrosión en medios acuosos ricos en iones de cloro cuando el número y el período de bicapa fueron 5 y 221,2 nm, respectivamente. Se observó que la formación de partículas de óxido de renio influye en el comportamiento electroquímico de los recubrimientos.
Keywords: Rhenium nitride; Multilayer coatings; Magnetron sputtering; Electrochemical behavior; Corrosion